Symbolic and systemic violence in media representations of aggression towards ambulance personnel in the Netherlands. Issue 1 (1st January 2016) - Cuijpers, Nicole; Brown, Patrick R.
Abstract : Violence towards public sector employees is perceived as a growing problem in a number of societies, attracting the attention of mass media, politicians and social scientists alike. In this article we discuss how national newspapers have reported aggression towards ambulance workers in the Netherlands. Our analysis is informed by Žižek's conceptualisations of less visible yet fundamental formats of violence, which he posits as vital for analysing narratives of subjective experiences of aggression. Based on quantitative analysis of newspaper articles describing such incidents between 2000 and 2010, we first provide insight into trends in media coverage. Following this, 121 news stories referring to the six most reported incidents are analysed using a critical discourse framework, paying particular attention to discursive constructs by which certain hegemonic explanations of the events were created and reinforced. Our findings denote a dramatic increase in reporting in the latter half of the decade, with large spikes of media interest around the key incidents. Analysis of central themes in the reporting of these key incidents, especially in terms of explanations and attributions of blame, notes the disproportionate influence of professionals' narratives, in contrast to those of often-marginalised individuals and groups who were depicted as the perpetrators of violence. This inequality in power is analysed as leading to particular (mis)representations of incidents and the related reproduction of stigmatising and othering discourses within newspaper coverage. Such tendencies in reporting came to centre upon discourses of ethnicity towards the latter part of the decade, reflecting more general tendencies within the Dutch public sphere at this time. We then apply our Žižekian framework to illuminate how subjective narratives of violence are embedded within the reproduction of symbolic and systemic violence. Such understandings of violence have vital implications for policy interventions.